STUDI LITERATUR: STRATEGI PROMOSI FILM BIOSKOP TERLARIS DI INDONESIA SEPANJANG SEJARAH - Melati Kusuma Wardhani, S.I.Kom, M.I.Kom, Melati Kusuma Wardhani, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2022)
Film is a medium of communication that has entertainment and artistic value for the audience. The development of films in Indonesia is growing rapidly, as can be seen from the growth of cinemas in various regions in Indonesia, where cinema is the main viewing medium for film connoisseurs. Therefore, the success of a film can be seen from the number of audiences who buy tickets for the film at the cinema. This study will describe what promotional strategies are used by film production houses for the highest-grossing films in Indonesia's history. The research methodology used in this study is in the form of a literature study by reviewing the journals of the research first. The results of this study indicate that the promotional strategies carried out by the house include placing advertisements on all media, approaching potential viewers, and evaluating the promotional activities that have been carried out.